(untitled) (Journal of Applied Oral Science, 2010)
This literature review article addresses the types and the main components of different etch-and-rinse and self-etch adhesive systems available in the market, and relates them to their function, possible chemical interactions and infuence of handling characteristics. Scanning electron microscopy (SEM) images are presented to characterize the interface between adhesives and dentin. Adhesive systems have been recently classifed according to their adhesion approaches in etch-and-rinse, self-etch and glass ionomer. The etch-and-rinse systems require a specifc acid-etch procedure and may be performed in two or three steps. Self-etch systems employ acidic monomers that demineralize and impregnate dental substrates almost at the same time. These systems are separated in one or two steps. Some advantages and defciencies were noted for etch-and-rinse and self-etch approaches, mainly for the simplifed ones due to some chemical associations and interactions. The SEM micrographs illustrate different relationships between adhesive systems and dental structures, particularly dentin. The knowledge of composition, characteristics and mechanisms of adhesion of each adhesive system is of fundamental importance to permit the adoption of ideal bonding strategies under clinical conditions.